2011
DOI: 10.1002/art.30325
|View full text |Cite
|
Sign up to set email alerts
|

Impact of synthetic and biologic disease-modifying antirheumatic drugs on antibody responses to the AS03-adjuvanted pandemic influenza vaccine: A prospective, open-label, parallel-cohort, single-center study

Abstract: Objective. To identify the determinants of antibody responses to adjuvanted split influenza A (H1N1) vaccines in patients with inflammatory rheumatic diseases.Methods. One hundred seventy-three patients (82 with rheumatoid arthritis, 45 with spondylarthritis, and 46 with other inflammatory rheumatic diseases) and 138 control subjects were enrolled in this prospective single-center study. Controls received 1 dose of adjuvanted influenza A/09/H1N1 vaccine, and patients received 2 doses of the vaccine. Antibody r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
5
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 46 publications
9
100
5
7
Order By: Relevance
“…In their study, Kapetanovic et al found similar or better seroconversion rates after influenza vaccination in a group of 62 patients receiving anti-TNF␣ without MTX (50% for H1N1, 51.6% for H3N2, and 58.1% for B) than in 18 healthy controls (50% for H1N1, 44.4% for H3N2, and 5.6% for B) (17). Moreover, in 3 studies that could not be included in the meta-analysis because the population included a combination of several inflammatory diseases, anti-TNF␣ did not reduce vaccine responsiveness (28,29,33).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In their study, Kapetanovic et al found similar or better seroconversion rates after influenza vaccination in a group of 62 patients receiving anti-TNF␣ without MTX (50% for H1N1, 51.6% for H3N2, and 58.1% for B) than in 18 healthy controls (50% for H1N1, 44.4% for H3N2, and 5.6% for B) (17). Moreover, in 3 studies that could not be included in the meta-analysis because the population included a combination of several inflammatory diseases, anti-TNF␣ did not reduce vaccine responsiveness (28,29,33).…”
Section: Discussionmentioning
confidence: 98%
“…Injection of a second dose, 1 month after the first dose, of pandemic H1N1 influenza vaccine was found to be more efficient than an injection of a single dose in patients with rheumatic inflammatory diseases (29). However, additional studies assessing the need of second booster doses in RA patients receiving treatments responsible for an impaired immune response are needed.…”
Section: Discussionmentioning
confidence: 99%
“…HI titers of 1:40 or greater have been shown to be protective against influenza in the general population [9]. Most of the studies evaluated suggest that RA patients using methotrexate and/or anti-TNF therapy (adalimumab, etanercept, infliximab) achieve an acceptable humoral response, although their response is lower than in healthy controls [10][11][12][13][14][15][16][17][18]. A recent study, in 2012, involving RA patients receiving tocilizumab, methotrexate (MTX) or the combination of the two suggest that there was no decreased effects of TCZ, and post-vaccination GMTs increased significantly for all strains of the influenza vaccine [19].…”
Section: Influenzamentioning
confidence: 99%
“…В боль-шинстве работ показано, что у больных РА, получавших метотрексат (МТ) и/или ингибиторы фактора некроза опу-холи α (иФНОα), достигаются приемлемые уровни гумо-рального поствакцинального ответа, хотя и более низкие, чем в контроле [24][25][26][27][28][29][30][31][32].…”
Section: гриппunclassified